Fuelling The Fuel That Fuels Us - New Sunday Times (2008)
WHEN we talk about fuel our thoughts revolve around energy sources for engines power plants or reactors In everyday parlance fuel is equated with petrol. We forget the greatest fuel of all: food. Even when we think of food as fuel it is in a most cursory manner. Yet fuel it is And the importance of that fuel has come to haunt us now that the price of the other fuel has shot through the barrel causing a ripple effect.